Respuesta del algodonero (Gossypium hirsutum) a la fertilización en suelos del valle del Alto Magdalena. - Gutiérrez Perdomo, Daniel (Instituto Colombiano Agropecuario, 2018)
Algodón-Gossypium herbaceum